UNIT 8.9 Preparation of Amniocytes for Interphase Fluorescence In Situ Hybridization (FISH). (1st April 2015) - Schwartz, Stuart
Abstract : FISH has been used to detect and clarify deletions and/or other structural rearrangements, and also has applications in interphase analysis. This unit describes preparation of uncultured amniotic fluid cells for FISH analysis. Cells are swollen, and then slides are prepared by standard methods. The cells are then fixed and permeabilized for subsequent FISH. An alternate protocol describes attachment of amniocytes to a glass or plastic surface followed by hypotonic swelling, fixation, and permeabilization for subsequent FISH. Interphase FISH analysis of amniotic fluid cells is also described. © 2015 by John Wiley & Sons, Inc.